Strengthening the Family Economy with Assistance in Marketing and Processing of Cassava Chips in Wonokerto Village Trenggalek, Indonesia - Novi Puji Lestari; Widhiyo Sudiyono (Universitas Muhammadiyah Sidoarjo, 2021)
Community service in the context of Marketing Assistance and cassava processing as a family economic booster in Wonokerto Trenggalek village. Cassava or cassava is a source of local carbohydrates in Indonesia which ranks third after rice and corn. This plant is the most potential raw material so that cassava has the potential as an important raw material for various food and industrial products. Cassava has a high carbohydrate content so it is considered a substitute for rice in some villages. The availability of cassava in some villages is finally considered as a normal and boring thing by the villagers or even the children who really don't like cassava or cassava. Related to this, it is necessary to have interesting cassava products that make people or children want to eat them. Based on these conditions, the service activity carried out by the team from the University of Muhammadiyah Malang aims to provide training on processing cassava into products that are worth selling such as chips. or cassava crackers and focus on marketing assistance such as packaging and branding on products so that they can be sold to various regions to help improve the economy of families in the village. active in preserving traditional specialties made from cassava.